The Hermeneutics and Listener Reception of the Song “Ma Syamamtul Warda” and the Lesson Plan - Barnabila, Muhammad Kesit; Mu'ammar, Naufal; Zakaria, Muhammad Thoriq Zizad; Yusuf, Kamal (Raja Zulkarnain Education Foundation, 2025)
Arabic songs that go viral on Indonesian social media are often enjoyed aesthetically without a deep understanding of the lyrics' meaning. One of them is a song entitled